2011
DOI: 10.1177/1471301211421074
|View full text |Cite
|
Sign up to set email alerts
|

Comparing day care at green care farms and at regular day care facilities with regard to their effects on functional performance of community-dwelling older people with dementia

Abstract: Day care at green care farms (GCFs) is a new care modality for community-dwelling older people with dementia. In view of the more physical and normal daily life activities available at GCFs than at RDCFs, we investigated whether functional decline differed between subjects from both day care settings. In this observational cohort study, primary caregivers of 47 subjects from GCFs and 41 subjects from RDCFs rated the subjects’ functional performance three times during one year. They also provided information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…In addition, they had a higher educational level than those at regular day care (Rokstad et al, ). The observations about sex, age and living conditions are in line with a study comparing participants at regular day care and FDC in the Netherlands (de Bruin et al, ). A literature review revealed that some men prefer social involvements that support their identity and where they can feel useful (Manthorpe & Moriarty, ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, they had a higher educational level than those at regular day care (Rokstad et al, ). The observations about sex, age and living conditions are in line with a study comparing participants at regular day care and FDC in the Netherlands (de Bruin et al, ). A literature review revealed that some men prefer social involvements that support their identity and where they can feel useful (Manthorpe & Moriarty, ).…”
Section: Discussionsupporting
confidence: 81%
“…Being physical active, spending time outdoors and being in social interactions with both other people and animals are the core components of the service offered at FDC (de Bruin et al, ; Ibsen et al, ). The present study underscores the benefit of spending time outdoors, as it was associated with a better quality of life and explained the variation in the quality of life reported by the participants at the FDC level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GCF group mainly consisted of married men who were on average younger than the subjects in the RDCF group that consisted mainly of widowed women. Although literature suggests gender, age and marital status to be related to several health outcomes (40-43), we did not detect differences in cognitive functioning, functional status and medication use between older people with dementia in both settings (44,45). It is therefore unlikely that the observed differences in dietary intake in the current study can be explained by health differences between both groups.…”
Section: Jnha: Clinical Neurosciencescontrasting
confidence: 71%
“…At the same time, however, it should be noted that the input of the PwD varied across the interviews, and that the input of family caregivers was often necessary to collect reliable and complete data. From an earlier study among PwD attending day care at a GCF or RDCF in the Netherlands, we learned that the average minimal mental state examination (MMSE) score in these groups was around 20, implying that cognitive impairment was mild to moderate (de Bruin, Oosting, Tobi, et al, 2012). Still, it was not always easy to understand their answers nor were they not always able to answer our questions.…”
Section: Discussionmentioning
confidence: 99%